THE IMPACT OF PREPARATION OF INITIAL PERMISSIVE DOCUMENTATION ON THE DURATION FOR REALIZATION OF INVESTMENT-CONSTRUCTION PROJECTS (Вестник университета)
The article deals with investigation of questions related to the preparation of initial permissive documentation and its impact on the duration of realization of investment construction projects. In regard to the existing preparation guidelines for initial permissive documentation, authors came to the conclusion that this system has essential shortcomings, and execution terms considerably increase the realization terms of investment-construction projects.